Identification And Determination of Levels the Drug Chemical Sibutramin Hydrochloride in Body Slimming Herbs Circulating in the City of Salatiga - Prisma Detty Nuryana; Endah Widhihastuti (Universitas Negeri Semarang, 2024)
Background: Sibutramine hydrochloride is strictly prohibited from being present in weight loss herbal medicines according to the regulations of the Indonesian National Agency of Drug and Food Control (Badan POM RI) No.KH.00.01.43. However, due to increasing competition, many traditional medicine producers seek greater profits by adding sibutramine hydrochloride (SH) to their products. Aim: This study aimed to establish the validity of the UV-VIS spectrophotometer method for analyzing sibutramine hydrochloride and to test the levels and content of sibutramine hydrochloride in weight loss herbal medicine samples sold in Salatiga City. Materials and Methods: A total of 8 samples of weight loss capsules obtained from traditional medicine stores in Salatiga City were subjected to qualitative and quantitative tests. Validation parameters included linearity, limit of detection (LoD), limit of quantification (LoQ), precision, and accuracy. Results: The study revealed a linear regression equation of y=0.0397x + 0.046 with r=0.9975 and r^2=0.9950, with a maximum wavelength of 223 nm. The LOD was 1.01 mg/L and LOQ was 3.37 mg/L. Precision, expressed as % RSD, was 0.147%, and percent recoveries (% recovery) were 98.263%, 89.337%, and 91.703%. Qualitative tests on each sample compared spectra and maximum wavelengths with standard sibutramine hydrochloride spectra, identifying samples A, B, C, E, and F as negative for sibutramine hydrochloride, while samples D, G, and H tested positive. Quantitative analysis determined sibutramine hydrochloride concentrations in weight loss herbal medicines using linear regression equations. The concentrations in samples D, G, and H were 6.0117 mg/L, 6.7254 mg/L, and 6.0117 mg/L, respectively. The percentage content of sibutramine hydrochloride in samples D, G, and H was 3.00%, 3.36%, and 3.00%, respectively. Conclusion: The UV-VIS spectrophotometer method is validated for analyzing sibutramine hydrochloride in weight loss herbal medicines across all tested parameters. Samples A, B, C, E, and F were found negative for sibutramine hydrochloride, whereas samples D, G, and H tested positive.